(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the effectiveness and practical aspects of using modern interactive methods in zoology lessons. The application of interactive approaches in the learning process enhances students’ cognitive activity, fosters the development of creative thinking, and contributes to the expansion of their scientific outlook. The paper presents an analysis of the impact of interactive methods on teaching efficiency, supported by practical experience and outcomes.